Strategic considerations on the development of Central Asia - Banskota, Mahesh; Karki, Archana S.; Croon, Frank W.; Council for Sustainable Development of Central Asia.; Zhongguo ke xue yuan.; International Centre for Integrated Mountain Development; Xianjiang Institute of Ecology and Geography; CoDoCA Conference 1998 èUrèumqi, China). (Bussum, The Netherlands Council for Sustainable Development of Central Asia, 1999)
Proceedings of 2nd CoDoCA Conference held in Urumqi, China, from September 13-18, 1998.
"Council for Sustainable Development of Central Asia, Chinese Academy of Sciences, International Centre for Integrated Mountain Development, Xinjiang Institute of Ecology and Geography"--Cover.
Keywords: Sustainable development -- Asia, Central; Asia, Central -- Economic conditions; Asia, Central -- Economic policy; Asia, Central -- Strategic aspects